The globalized library : American academic libraries and international students, collections, and practices - Luckert, Yelena, 1962-; Carpenter, Lindsay Inge (Association of College and Research Libraries, 2019)
Many academic institutions count internationalization among their most important strategic goals and priorities: To be globally competitive, colleges and universities need to produce globally conscious graduates. In addition to hiring practices that are beginning to emphasize librarians with international experience and language expertise, and the traditional role of libraries collecting foreign acquisitions, new trends are emerging that help address international student education and highlight library initiatives that can make a huge difference in student success and retention. In five sections--Information Literacy; Outreach & Inclusion; Collections & Digital Humanities; Establishing Libraries & Services Abroad; and Career & Professional Development--The Globalized Library collects chapters from practitioners across the world detailing how their work is globalized and demonstrating new ways to address language and cultural differences, access issues abroad, the international purchase and processing of materials, and information literacy needs of students from all over the world. It explores the use of campus partnerships to create specially designed programs and learning opportunities for international students, providing support to students studying abroad, creating online teaching tools, and establishing American-style libraries at satellite campuses in countries where access to information is highly restricted. Academic libraries are deeply involved in all aspects of the globalization of our institutions and community at large. As well, academic institutions have an obligation to all students, foreign or domestic, to help them succeed academically and become information-literate citizens of the world. As the center of campus life, academic libraries need to develop new and innovative approaches to welcome and educate students in a holistic sense and become a true campus partner in this enterprise.